PENGARUH PENDEKATAN SAINTIFIK TERHADAP HASIL BELAJAR PADA MATA PELAJARAN IPA DI KELAS III SD NEGERI 101766 BANDAR SETIA - Budi Mawarti (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2023)
This study investigates the influence of the scientific approach on the learning outcomes of third-grade students in science at SD Negeri 101766 Bandar Setia. As a quasi-experimental research, the study aims to determine the efficacy of the scientific approach compared to traditional teaching methods. The population comprised 50 third-grade students, divided into experimental and control groups. The experimental group received instruction via the scientific approach, while the control group was taught using conventional methods. Data collection involved pretests and posttests to measure learning outcomes, complemented by observations and questionnaires to gauge student engagement and teacher feedback. Results indicated a significant improvement in the experimental group’s performance, suggesting that the scientific approach enhances student understanding and retention in science. This study underscores the importance of adopting interactive and student-centered teaching methods to improve educational outcomes.